Profile of Problem Based Learning to Improve Students' Critical Thinking Skills - Shofiyatul Masruro; Elok Sudibyo; Tarzan Purnomo (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2021)
This article was created to identify the effect of the Problem Based Learning model in improving students' critical thinking. The data collection method is in the form of a literature study. This article explains that problem-based learning is a learning model that focuses on students' solving problems in physics concepts. Critical thinking is the student's ability to analyze and evaluate the information received to conclude appropriately. The results of the literature study showed an increase in students' critical thinking skills in the learning process with the Problem Based Learning (PBL) learning model. The application of Problem Based Learning has an average increase of about 50% after the learning pattern is applied. The existence of the PBL learning model is effectively used to improve students' critical thinking, which incidentally in solving physics concepts requires the ability to analyze and evaluate to conclude.